Effects of physical exercise on sensory perception and hedonic response - Jarry, Lucile Claire (Kansas State University, 2016)
Sensory perception and hedonic response to foods and beverages depend not only on the characteristics of the food or beverage product, but also on the physiological and psychological state of the person consuming it. Physical exercise provokes physiological changes in human subjects including dehydration through sweat loss and depletion of energy stores, and emotional changes including increased fatigue and vigor; as such it is expected to affect the sensory and hedonic response to foods consumed immediately post-workout. Exercise and proper diet are both well-recognized components of a healthy lifestyle; it is therefore critical to understand how an acute bout of exercise or a chronic training regimen might affect the eating behavior of the exerciser. This review examines published studies -- both interventional and observational -- on the effect of acute and chronic physical exercise on thirst, hunger, perception and liking of the five basic tastes, and macronutrient choice. This review also touches on macronutrient choice and psychological factors of food choice such as compensatory eating and food restraint. Results suggest that acute exercise of a certain threshold intensity effects consistent perceptual and hedonic changes across the population: immediate hunger suppression, osmoregulatory thirst, increased palatability of salt, increased perception and palatability of sweetness, and decreased perception and palatability of sourness. Effects on bitter and umami appear more limited. However, individual metabolic and psychological variation modulate these effects, and the effects of chronic exercise are complicated by concurrent lifestyle changes and not properly understood through observational studies alone.
Keywords: Sensory perception; Hedonic response; Physical exercise